2001
DOI: 10.1190/1.1444979
|View full text |Cite
|
Sign up to set email alerts
|

Depth‐domain velocity analysis in VTI media using surfaceP-wave data: Is it feasible?

Abstract: The main difficulties in anisotropic velocity analysis and inversion using surface seismic data are associated with the multiparameter nature of the problem and inherent trade-offs between the model parameters. For the most common anisotropic model, transverse isotropy with a vertical symmetry axis (VTI media), P-wave kinematic signatures are controlled by the vertical velocity V 0 and the anisotropic parameters and δ. However, only two combinations of these parameters-NMO velocity from a horizontal reflector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…Le Stunff et al (2001) demonstrated that the success of the tomographic inversion procedure was ensured by the reflection traveltimes for the bottom reflector near the left edge of the model, where the intermediate interface is dipping. Indeed, P-wave moveout in VTI media is controlled by the zero-dip NMO velocity and parameter η only if the medium above the reflector is laterally homogeneous.…”
Section: Vti Model With a Curved Interfacementioning
confidence: 98%
See 1 more Smart Citation
“…Le Stunff et al (2001) demonstrated that the success of the tomographic inversion procedure was ensured by the reflection traveltimes for the bottom reflector near the left edge of the model, where the intermediate interface is dipping. Indeed, P-wave moveout in VTI media is controlled by the zero-dip NMO velocity and parameter η only if the medium above the reflector is laterally homogeneous.…”
Section: Vti Model With a Curved Interfacementioning
confidence: 98%
“…Following Le Stunff et al (2001), we consider P-wave moveout inversion for a model composed of two homogeneous layers (VTI and isotropic) separated by a curved interface ( Figure 2.11). P-wave reflection traveltimes for both interfaces were calculated by anisotropic ray tracing; the modeling parameters are listed in Table 2.1.…”
Section: Vti Model With a Curved Interfacementioning
confidence: 99%
“…However, the anisotropy parameters to use are not easy to determine. Transverse isotropy is often described in terms of the Thomsen parameters ε and δ (Thomsen, 1986), and there has been considerable published work addressing the question of Presented how to extract these parameters from surface seismic data, focusing primarily on the application of nonhyperbolic velocity analysis and traveltime inversion (e.g., Alkhalifah and Tsvankin, 1995;Grechka and Tsvankin, 1998a, b;Grechka and Tsvankin, 1999;Grechka, Pech, et al, 2001;Le Stunff et al, 2001) or on the analysis of joint P-and converted-wave data (Grechka, Theophanis, and Tsvankin, 1999;Sayers, 1999;Grechka, Pech, and Tsvankin, 2002;van der Baan and Kendall, 2002). We present an independent method of estimating the effective anisotropy parameters from surface P-wave reflection seismic data.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, this is not the case, especially when well data are not available. Earlier studies showed that if only surface P-wave data are available, it will be difficult if not impossible to resolve accurately the three quantities V z , , and ␦ ͑Le Stunff et al, 2001;Sarkar and Tsvankin, 2004͒. When relying on surface data only, we suggest using the near offsets in the IMO domain to perform a standard isotropic interval-velocity analysis ͑such as depth residual moveout and tomography͒ prior to the estimation of and ␦.…”
Section: Wrong V Zmentioning
confidence: 98%